2x-26=4x+46

Simple and best practice solution for 2x-26=4x+46 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-26=4x+46 equation:



2x-26=4x+46
We move all terms to the left:
2x-26-(4x+46)=0
We get rid of parentheses
2x-4x-46-26=0
We add all the numbers together, and all the variables
-2x-72=0
We move all terms containing x to the left, all other terms to the right
-2x=72
x=72/-2
x=-36

See similar equations:

| 5x-51=6x+130 | | -15=0+0x | | p−8–1=–2 | | 4(2x-8)=6x+14 | | -6=5m-41 | | 5x-51=6x-130 | | 3(2+1)-3g=10 | | 5(x-10)+11=9x+1 | | 5x-51=5x+50 | | 2(3a-2)=8 | | 0.3=-3t | | 4p-2+9p=4(2p-3)-7p | | a+3+29=-1+39+4 | | p+30=20-p | | 5x-51=6x+71 | | 5/8y+4=3/8y+12 | | -1/3x+21=0 | | 13.4-3.5a=33 | | 21k+23=19 | | x+12.1=7.53 | | 12=-28+6b | | 3t+9t=144 | | (9/k)=(-3/20) | | 2(1-2)+6g=12 | | -124-4x=-15x+96 | | 11=9x+1 | | 12=-6x-24 | | (8.5)·(-3)=a | | x=x-17+73 | | -3-7c=7-7c | | -1/5m-9=-13 | | n/3+6=0 |

Equations solver categories